Point prevalence survey of urinary catheterisation in care homes and where they were inserted, 2012. Issue 4 (July 2014) - McNulty, CAM; Verlander, NQ; Turner, K; Fry, C
The extent to which the use of catheter care bundles and other interventions has led to a reduction in urinary catheterisation rates is unknown. We aimed to determine current urinary catheterisation rates in care homes with residents over 65 years old, and determine the extent to which residents are discharged from the hospital setting with urinary catheters. A point prevalence questionnaire survey was used in care homes that looked after residents over 65 years in six UK health boards or primary care trusts, to determine urinary catheterisation rates, and where these catheters were inserted. Questionnaires for 445 of 461 care homes (96.5%) were completed, 425 of 445 care homes cared for residents over 65 years; 888 (6.9%) of 12, 827 residents had a urethral (82.5%) or supra-pubic (17.5%) urinary catheter. Over half of all catheters (both urethral and suprapubic, 57.4%, 509 of 888 catheters), and 3.1% of all residents had a catheter inserted while the residents were hospital inpatients, and then discharged back to the care home still catheterised. There was a significant variation in urinary catheterisation rates in the care homes surveyed, and rates remain similar to previous English surveys in 2003 and 2009. More still needs to be done to understand the variation in urinary catheterisation rates in care homes and reduce these rates, including the numbers of residents that are discharged from hospital with a urinary catheter.